2015
DOI: 10.3109/01902148.2015.1046199
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids can affectPseudomonas aeruginosa(ATCC 27853) internalization and intracellular calcium concentration in cystic fibrosis bronchial epithelial cells

Abstract: These findings suggest that if internalization of P. aeruginosa reduces infection, GC therapy would increase the risk of pulmonary infection by decreasing the internalization of P. aeruginosa in CF cells, but GCs may improve airway hydration by increasing the intracellular Ca(2+) concentration. Whether the benefits of GC treatment outweigh the negative effects is questionable, and further clinical studies need to be carried out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…A plausible explanation is the treatment of aspergillosis by glucocorticoids, which could impair internalization and phagocytosis of P . aeruginosa by CF respiratory epithelial cells [12].…”
Section: Discussionmentioning
confidence: 99%
“…A plausible explanation is the treatment of aspergillosis by glucocorticoids, which could impair internalization and phagocytosis of P . aeruginosa by CF respiratory epithelial cells [12].…”
Section: Discussionmentioning
confidence: 99%
“…Irrespective of whether or not CFTR is a receptor for P. aeruginosa, it is well described from in vitro and in vivo studies that CF cells do show P. aeruginosa internalization (4,29,35,39). More recent studies have shown that stimulation of bronchial epithelial cells with IL-22 and a cytomix (IL-1␤, TNF-␣, and IFN-␥) decreases P. aeruginosa internalization in both CF and non-CF cells (24) and that glucocorticoids can reduce P. aeruginosa internalization in cystic fibrosis bronchial epithelial cells (27). Nonmucoid P. aeruginosa may hide in epithelial cells to escape the host innate immune defense or secrete toxins to efficiently kill host cells (30).…”
Section: Lxa 4 Reduces P Aeruginosa Intracellular Invasion and Transmentioning
confidence: 97%
“…Bronchoalveolar lavages of CF patients show elevated levels of IL-6 and IL-8 (Bonfield et al 1995), and pre-treatment of CF AECs with IL-6 or IL-8 increases P. aeruginosa internalisation, suggesting that appropriate inflammatory responsiveness might hamper the establishment of chronic colonisation in CF patients (Hussain et al 2015). Despite controversy, glucocorticoids are used as anti-inflammatory agents; however, it has been shown that concomitant treatment of CF airway cells with glucocorticoids and IL-6 decreases bacterial internalisation, in turn reducing bacterial clearance and possibly increasing the risk of pulmonary infection in CF patients (Hussain et al 2015). Heightened release of IL-1β is also central to the lethal effect of acute P. aeruginosa infection and mice deficient for the IL-1 receptor show improved host defence against infection in the lung (Schultz et al 2002(Schultz et al , 2004.…”
Section: Microbial Clearance Facilitated By Cellular Desquamation and Apoptosis Of Infected Aecs: P Aeruginosamentioning
confidence: 99%